Theories of Learning for the Workplace : building blocks for training and professional development programmes - Dochy, Filip; Gijbels, David; Segers, Mien (London, New York : Routledge, 2011)
"Psychological Theories of Learning in the Workplace is an advanced textbook that provides a fascinating overview of the most important psychological theories of learning and their practical application to organisational or workplace learning. It explains theories on: Adult learning, Workplace learning, Informal learning, Reflective practice, Experiential learning, Organisational and interorgani-sational expansive learning. Rigorously underpinned with contemporary psychological theories of learning, this book will be essential reading for all trainee and practicing educational psychologists, organisational psychologists, researchers and students in the field of Lifelong learning, Educational policy makers, students, researchers and teachers in Higher Education. A unique feature of this textbook is that each chapter combines a case study by a situated academic researcher and a co-author from business or industry together with a detailed overview of the psychological theory underpinning the learning process. The chapters have been written by key figures in education, psychology, and cognitive science and encompass a comprehensive range of conceptual perspectives on learning theory offering a wealth of new insights to support innovative research directions"
Includes Bibliographical References and Index.
Keywords: Adult learning; Organizational learning; professional development